2013
DOI: 10.1089/ten.tea.2013.0097
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Functional Ocular Surface by Acellular Porcine Cornea Matrix Scaffold and Limbal Stem Cells Derived from Human Embryonic Stem Cells

Abstract: Limbal stem cells (LSCs) derived from human embryonic stem cells (hESCs) hold great potential for cell-based therapies for ocular surface diseases. The cell-based therapies mainly depend on an appropriate differentiation proposal with a high efficiency and on a suitable scaffold. In this study, we aimed to establish a feasible and efficient strategy for inducing hESCs into LSC-like cells by the LSC conditioned medium. The induced cells possessed the similar morphologic characteristics and expression of normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 50 publications
0
34
0
1
Order By: Relevance
“…The mesh structure in the matrix layer can provide space for the growth of mesenchymal cells and the exchange of metabolites. In addition, APCSs can also be used as seed carriers (21). Our previous animal study (13), through implantation of APCSs into rabbit corneal pockets and mouse subcutaneous tissue, showed that the APCS is unable to stimulate a host response in the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…The mesh structure in the matrix layer can provide space for the growth of mesenchymal cells and the exchange of metabolites. In addition, APCSs can also be used as seed carriers (21). Our previous animal study (13), through implantation of APCSs into rabbit corneal pockets and mouse subcutaneous tissue, showed that the APCS is unable to stimulate a host response in the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…With the use of specific media and growth factors, ESCs have been cultured in vitro into other cell types, including skeletal muscle, endothelial cells, chondrocytes and myocardiocytes, among others [3,4]. In later experiments on these stem cells, researchers have produced eyeball and vocal cord structures [5,6].…”
Section: Types Of Stem Cellsmentioning
confidence: 99%
“…Having produced the decellularized cornea there is then a choice of which cells to use to repopulate the construct for transplantation onto the injured cornea to promote the repair. [24,25] For example, human embryonic stem cells have been differentiated into LSC-like cells and used to repopulate acellular pig corneal matrix and following transplantation in a rabbit LSCD model was able to reconstruct the surface of the cornea and maintain the cornea/conjunctiva boundary. [26] Epithelial cells have also been isolated from human AM and seeded into decellularized pig cornea and shown to stratify after 7 d. When transplanted into a rabbit model it was found to integrate well into the host tissue and maintain corneal clarity.…”
Section: Amniotic Membranementioning
confidence: 99%